A general soft-enveloping strategy in the templating synthesis of mesoporous metal nanostructures - Fang, Jixiang (2018)
Metal species have a relatively high mobility inside mesoporous silica; thus, it is difficult to introduce the metal precursors into silica mesopores and suppress the migration of metal species during a reduction process. Therefore, until now, the controlled growth of metal nanocrystals in a confined space, i.e., mesoporous channels, has been very challenging. Here, by using a soft-enveloping reaction at the interfaces of the solid, liquid, and solution phases, we successfully control the growth of metallic nanocrystals inside a mesoporous silica template. Diverse monodispersed nanostructures with well-defined sizes and shapes, including Ag nanowires, 3D mesoporous Au, AuAg alloys, Pt networks, and Au nanoparticle superlattices are successfully obtained. The 3D mesoporous AuAg networks exhibit enhanced catalytic activities in an electrochemical methanol oxidation reaction. The current soft-enveloping synthetic strategy offers a robust approach to synthesize diverse mesoporous metal nanostructures that can be utilized in catalysis, optics, and biomedicine applications.